Tri-stimuli-responsive biodegradable theranostics for mild hyperthermia enhanced chemotherapy. (May 2017) - Lu, Nan; Huang, Peng; Fan, Wenpei; Wang, Zhantong; Liu, Yijing; Wang, Sheng; Zhang, Guofeng; Hu, Junkai; Liu, Wenfei; Niu, Gang; Leapman, Richard D.; Lu, Guangming; et al.
Abstract: The combination of hyperthermia and chemotherapy is able to greatly enhance the treatment efficacy mainly due to the synergistic interactions between these two treatments. In this study, we propose a new concept of mild hyperthermia enhanced chemotherapy to explore and validate the synergistic mechanism in vitro and in vivo . To do this, a novel kind of biodegradable nanotheranostics based on copper sulfide doped periodic mesoporous organosilica nanoparticles (CuS@PMOs) was constructed via an in situ growth method for light-triggered mild hyperthermia and drug delivery. The as-prepared CuS@PMOs exhibit a high doxorubicin (DOX) loading capacity of 470 mg/g. The DOX release from CuS@PMOs can be precisely controlled by three stimuli, including intracellular glutathione (GSH), acidic environment in tumor cells, and external laser irradiation. Most intriguingly, mild hyperthermia induced by laser-irradiated CuS nanoparticles can dramatically improve the cell uptake of nanotheranostics both in vitro and in vivo, thus significantly enhancing the chemotherapeutic efficacy for complete tumor growth suppression without recurrence. Meanwhile, the fluorescence recovery following the DOX release can be used as an indicator to monitor the chemotherapeutic progress.